Morphological differences between planes of section do not influence the electrophysiological properties of identified rat dorsal motor nucleus of the vagus neurons - y Valenzuela, Isabel Martinez-Peña (2004)
Recent cytoarchitectonic studies have shown that the dorsal motor nucleus of the vagus (DMV) comprises neurons with different morphological features. Our own studies, conducted in horizontal brainstem slices, have shown that DMV neurons projecting to stomach areas can be distinguished from neurons projecting to the intestine on the basis of their electrophysiological as well as morphological properties. The majority of the in vitro experimental investigations, however, have been conducted on coronal brainstem slices. The aim of the present study was to assess whether the electrophysiological properties of DMV neurons are due to intrinsic membrane properties of the neurons or are dependent upon the plane of section, i.e., coronal vs. horizontal, in which the brainstem is cut. The fluorescent retrograde tracer DiI was applied to either the stomach or intestine of rats. Whole cell recordings were subsequently made from labeled DMV neurons in thin brainstem slices sectioned in either the horizontal or coronal plane. In the horizontal plane, both the somata and the dendritic tree of gastric-projecting neurons were smaller than intestinal-projecting neurons. In the coronal plane, however, apart from a smaller soma diameter in gastric-projecting neurons, morphological differences were not found between the groups. The electrophysiological differences observed between the groups were, however, consistent in both planes of section, that is, intestinal-projecting neurons had larger and longer afterhyperpolarization (AHP) as well as slower frequency–responses to depolarizing stimuli than gastric-projecting neurons. Our data suggest that intrinsic rather than morphological features govern the electrophysiological characteristics of DMV neurons.